2017
DOI: 10.1142/s0218810417500277
|View full text |Cite
|
Sign up to set email alerts
|

X-ray Guided Steroid Injections for Proximal Interphalangeal Joint Osteoarthritis of the Fingers

Abstract: X-ray guided injections are a simple procedure which can be effectively performed in the out- patient setting, resulting in satisfied patients with improved hand function and pain scores.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…In our unit, we inject joints in the hand and wrist under X-ray guidance. Several studies have shown that the use of imaging increases analgesic affect (Miller et al., 2017; Swindells et al., 2010). This may be due to improved positioning into the joint of the needle.…”
Section: Discussionmentioning
confidence: 99%
“…In our unit, we inject joints in the hand and wrist under X-ray guidance. Several studies have shown that the use of imaging increases analgesic affect (Miller et al., 2017; Swindells et al., 2010). This may be due to improved positioning into the joint of the needle.…”
Section: Discussionmentioning
confidence: 99%